Effects of low pH and Pb2+ stress on living cyanobacterium, Phormidium angustissimum West & G.S.West: A test of its feasibility as a living biosorbent - Ruangsomboon, Suneerat; Wongrat, Ladda; Choochote, Sakchai; Ganmanee, Monthon; Saparnklang, Atiya (My University, 2013)
Pb2+ adsorption by the living cyanobacterium, Phormidium angustissimum followed the Langmuir adsorption model, with the maximum adsorption capacity (q max) of 295.4 ± 13.8 mg g-1. This result suggests that P. angustissimum is a promising living biosorbent to remove Pb2+ from wastewaters. Living biosorbents are better able to remove Pb2+ from wastewater than dead biosorbents, however there are practical limitations for their use are encountered in extreme conditions such as low pH and high Pb2+ concentration. The feasibility of using cyanobacterium, P. angustissimum, as a living biosorbent for the extraction of Pb2+ from wastewater was studied by investigating its photosynthestic performance and tolerance under Pb2+ (0-5 mg L-1) contamination and low pH (pH 3-7). Decreased photosynthetic performance caused by Pb2+ contamination and low pH stress was detected in this study by means of a reduction of the maximum photochemical efficiency of PSII (Fv/Fm). Detoxification mechanisms of P. angustissimum on Pb2+ appeared to increase its intracellular polysaccharides (IPS), exocellular polysaccharides (EPS), and protein. Living P. angustissimum could increase the pH of the solution which resulted in Pb2+ precipitation. The unique ability of P. angustissimum to remove Pb2+ and to grow under toxic conditions, demonstrated herein, indicates that it is a promising living biosorbent for mildly acidic water contaminated with Pb2+ in bioremoval systems in the which pH is not lower than 5 and Pb2+ is not higher than 5 mg L-1. © 2013 Springer Science+Business Media Dordrecht.
Keywords: Chlorophyll fluorescence; Detoxification; Langmuir isotherm; Polysaccharide; Protein; Wastewater treatment